A Detroit story urban decline and the rise of property informality - Herbert, Claire W., 1984- (University of California Press, 2021)
"Bringing to the fore a wealth of original research, A Detroit Story examines how the reclamation of abandoned property has been shaping the city for decades. Herbert lived in Detroit for almost five years to get a ground-view sense of how this process molds urban areas--participating in community meetings and tax foreclosure protests, interviewing various groups, following scrappers through abandoned buildings, and visiting squatted houses and gardens. Herbert found that there's a disjunction between different types of property reclaimers: lifestyle back-to-the-earth new residents, primarily more privileged, whose practices are often formalized by local policies, and longtime more disempowered residents, often representing communities of color, whose practices are marked as illegal and illegitimate. She teases out how the divergent treatment of these two approaches to informally claiming property reproduces long-standing inequalities in race, class, and property ownership. More generally, A Detroit Story examines how the attempt to formalize property informality in cities harms the most vulnerable"--